Juror Bias in Perceptions of Lesbian Intimate Partner Violence - Wasarhaley, Nesa Elizabeth (2014)
Homophobic attitudes pervade our society and specifically our justice system, which negatively impact legal protection for lesbian victims of intimate partner violence (IPV). Juror stereotypes about IPV victims and perpetrators as well as their biases based on sexual orientation may be a hindrance to IPV cases being reported and successfully prosecuted. The primary goal of this study was to investigate the impact that mock jurors’ attitudes toward homosexuals and gender roles, and their acceptance of myths about domestic violence had on their perceptions of lesbian IPV. Heterosexual undergraduate students (N = 259) read a trial summary in which the defendant was charged with physically assaulting her same-sex partner. The trial varied as to whether the victim and defendant were depicted via images as feminine or masculine and thus were either stereotypical or counter-stereotypical. Participants rendered verdicts and made judgments about the victim and defendant (e.g., credibility, sympathy). Results indicated that a masculine victim indirectly increased the likelihood of rendering guilty verdicts by increasing anger toward the defendant. Participants with negative attitudes toward lesbians rated the defendant as low in credibility, and when the victim was masculine, these participants had more anger toward the defendant than participants with more positive attitudes. Participants high on hostile sexism (i.e., attitudes that justify male power) or domestic violence myth acceptance (i.e., endorsement of false beliefs that justify physical aggression against intimate partners) minimized the seriousness of the incident, which decreased the likelihood of rendering guilty verdicts. Participants low in benevolent sexism (i.e., feelings of protectiveness toward women that support traditional gender roles) rated the incident as lower in seriousness and had less anger toward the defendant for a feminine victim paired with a masculine defendant. Participants high in benevolent sexism rated the incident as less serious when the victim and defendant were both feminine, and had more anger toward the defendant when the victim was masculine and the defendant was feminine. Results provide insight into the relationships between victim and defendant stereotypicality and individual differences in attitudes on mock juror decision-making in lesbian IPV cases